Analysis of the Fear of Missing Out (FoMO) Phenomenon in Instagram Social Media Use Among Generation Z - Rizky Fadilla (Nusantara Society Lab, 2025)
This study explores the phenomenon of Fear of Missing Out (FoMO) among Generation Z in their use of Instagram as a social media platform. The problem arises from the increasing tendency of young people to experience anxiety, social pressure, and identity challenges when exposed to constantly updated online content and trending activities. Using a qualitative approach with phenomenological methods, this research examines the subjective experiences of selected informants to capture how FoMO is felt, expressed, and interpreted in daily digital interactions. The analysis is supported by theoretical frameworks such as FoMO theory, Social Identity theory, and the Uses and Gratifications approach. The findings reveal that FoMO manifests in repeated scrolling behavior, impulsive decision-making to join social trends, and the need for social validation, which collectively influence how Gen Z constructs their self-image and social relationships. Instagram’s visual and interactive features were found to intensify these experiences. The study concludes that FoMO is not merely a psychological condition but also a social communication process shaped by identity, recognition, and the pursuit of belonging in digital culture .